2014
DOI: 10.1039/c4sc00584h
|View full text |Cite
|
Sign up to set email alerts
|

A precision structural model for fullerenols

Abstract: An explicit structural model was developed and verified for fullerenols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 35 publications
4
34
0
7
Order By: Relevance
“…When dissolved in aqueous solution, they form nanoparticles as polyanion nano-aggregates, and the nanoparticle size is reduced in more acidic solution [40][41][42] . It was reported that the smaller sized nanoparticles may allow deeper penetration into tumour tissues 43 .…”
Section: Discussionmentioning
confidence: 99%
“…When dissolved in aqueous solution, they form nanoparticles as polyanion nano-aggregates, and the nanoparticle size is reduced in more acidic solution [40][41][42] . It was reported that the smaller sized nanoparticles may allow deeper penetration into tumour tissues 43 .…”
Section: Discussionmentioning
confidence: 99%
“…1. Видно, что там присутствуют характерные для фуллере-нолов пики поглощения при волновых числахν, равных , cm n [6][7][8]. Нагрев образца до 90…”
Section: (поступила в редакцию 23 января 2018 г)unclassified
“…3 спектр сигнала ЯМР 13 C (10 kHz) в целом соответствует данным других ра-бот [6,8,9]. В отличие от сигнала чистого фуллерена он имеет несколько пиков, обусловленных существованием различных связей углерода с присоединенными груп-пами (их соотнесение можно найти, например, в [8]).…”
Section: (поступила в редакцию 23 января 2018 г)unclassified
See 2 more Smart Citations